2014
DOI: 10.1128/aem.00348-14
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Salmonella Subtypes Differ between Two U.S. Produce-Growing Regions

Abstract: bSalmonella accounts for approximately 50% of produce-associated outbreaks in the United States, several of which have been traced back to contamination in the produce production environment. To quantify Salmonella diversity and aid in identification of Salmonella contamination sources, we characterized Salmonella isolates from two geographically diverse produce-growing regions in the United States. Initially, we characterized the Salmonella serotype and subtype diversity associated with 1,677 samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 68 publications
2
54
0
Order By: Relevance
“…Recently, Newport, Cerro, and Thompson were reported as the most common serovars of isolates from produce-growing regions of New York State, while Saphra, Newport, and S. enterica subsp. diarizonae serovar 50:r:z were most common in south Florida (56). The disparities among studies could represent differences in either sampling methodologies or the discriminatory powers of the different typing methods.…”
Section: Figmentioning
confidence: 99%
“…Recently, Newport, Cerro, and Thompson were reported as the most common serovars of isolates from produce-growing regions of New York State, while Saphra, Newport, and S. enterica subsp. diarizonae serovar 50:r:z were most common in south Florida (56). The disparities among studies could represent differences in either sampling methodologies or the discriminatory powers of the different typing methods.…”
Section: Figmentioning
confidence: 99%
“…Epidemiological investigations indicate that Salmonella, pathogenic Escherichia coli, and Listeria monocytogenes stand out as the most important bacterial agents linked to fresh-produce disease outbreaks (3,(5)(6)(7). Recent studies have reported the occurrence and high diversity of these microorganisms in the environment or in close areas of produce farming areas (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…One of the nonhost reservoirs of Salmonella on which considerable effort has focused is surface water, which poses a potential public health risk through consumption, indirect consumption (for example, irrigation of edible horticultural crops), or direct contact. A number of studies have characterized the distribution of Salmonella isolates from different water sources (5)(6)(7)(8)(9)(10). In evaluations of surface water for Salmonella isolates, multiple serotypes are often identified from a single environmental sample, indicating the diversity of this genus in the environment.…”
mentioning
confidence: 99%
“…Salmonella serotypes isolated from surface waters are often not clinically common (4)(5)(6)(7)(8)(9)(10)(11)(12) and often include serotypes of Salmonella enterica subsp. enterica, Salmonella enterica subsp.…”
mentioning
confidence: 99%